PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CV. ARISTA JAYA MAGETAN - Ayuk Fitrianingsih; Deviliya Arga Manggala; Dian Fitria (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study aimed to determine the effect of the work environment and work discipline either simultaneously or partially on employee performance CV Arista Jaya Magetan. Determination of the sample in this study used a population sample that employees CV Arista Jaya Magetan some 62 people. Data collection using questionnaires and interviews. In a technique used to analyze the data analyst validity test, reliability test, normality test, the assumptions of classical, linear regression test, t test and F test were processed with SPSS for Windows version 17.0. results of data analysis showed that the work environment has a positive and significant impact on employee performance. Labor discipline has a positive and significant impact on employee performance. Work environment and work discipline simultaneously have a positive and significant impact on employee performance.  Keywords: Work Environment, Discipline, Employee Performance